2011
DOI: 10.1007/s00033-011-0119-2
|View full text |Cite
|
Sign up to set email alerts
|

Polynomial, rational and analytic first integrals for a family of 3-dimensional Lotka-Volterra systems

Abstract: Abstract. We extend the study of the integrability done by Leach and Miritzis (J. Nonlinear Math. Phys. 13 (2006), 535-548) on the classical model of competition between three species studied by May and Leonard (SIAM J. Appl. Math. 29 (1975), 243-256), to all real values of the parameters. Additionally our results provide all polynomial, rational and analytic first integrals of this extended model. We also classify all the invariant algebraic surfaces of these models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
50
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 23 publications
2
50
0
2
Order By: Relevance
“…In [8] the authors showed for the case a + b = −1, system (2) has also a first integral. We also note that the existence of first integrals for system (2) imply the existence of invariants for system (1).…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In [8] the authors showed for the case a + b = −1, system (2) has also a first integral. We also note that the existence of first integrals for system (2) imply the existence of invariants for system (1).…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
“…Our main results on the polynomial integrability of system (2) were obtained in [8] and are: For proving our main result concerning the existence of first integrals of Darboux type we shall use the invariant algebraic surfaces of system (2). This is the basis of the Darboux theory of integrability.…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…when such differential systems have first integrals (see for instance [1,2,4,5,6,7,8,17,18,22]),or • in their periodic orbits (see for example [9,10,11,13,16,20,24,25,26]). …”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
“…system (1) with m = 2, having two real or complex invariant straight lines taking into account their multiplicity was given in [2], and extensions to dimension 3 are given in [11]. Now we do the characterization of all polynomial differential systems in R 2 having an invariant conic and a Darboux invariant.…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%